PWE-058 Postprandial suppression of reflux by a raft forming alginate (gaviscon advance) compared to a simple antacid: technical assessment of pH-impedance monitoring and clinical feasibility study in gastro-oesophageal reflux disease (GORD) patients. (28th May 2012) - Sweis, R; Anggiansah, A; Wong, T; Fox, M R
Abstract : Introduction: Proton Pump Inhibitors (PPI) reduce acid reflux but not the frequency or proximal extent of reflux events that are a cause for persistent symptoms on PPI. Alginate preparations containing bicarbonate are effective for short-term control of reflux symptoms by formation of a viscous raft above the meal and acid neutralisation. However mechanistic studies have found equivocal effects of alginates on reflux suppression. It is unclear whether this was due to lack of effect, study power or technical issues. Aim: (i) technical assessment of pH-impedance equipment (Sandhill) in patients taking acid and reflux suppressants (ii) in vivo assessment of mechanistic effects of Gaviscon Advance (GA; Reckitt Benckiser) and Milk of Magnesia (MM; Boots) on postprandial reflux. Methods: (i) To assess effects on signal detection 10 patients took 10 ml GA or MM followed by repeated, single 10 ml swallows of orange juice (pH 4) until chemical and volume clearance was detected (ii) A randomised, controlled, double-blind, cross-over clinical study in 20 GORD patients (9 male: 11female; age 25–63) referred for investigation of reflux symptoms. On subsequent days at the beginning and end of a 24 h monitoring period, patients were randomised to receive either 10 ml GA or MM (both mint flavoured) after a mixed test meal (600 kcal). Postprandial distal and proximal reflux events (acid and non-acid) were documented over 4 h by pH-impedance with the patient in the upright, seated position. Results: (i) Technical: After intake of 10 ml GA or MM the pH and impedance signal fully recovered after median 6 (2–12) and 4 (2–10) swallows of orange juice. (ii) Clinical: During the 4 h postprandial observation acid exposure time (mean 2.3% (SD 3.3%) vs 3.4% (4.2%), p=0.296) and number of distal reflux events (20.5 (13.6) vs 22.5 (9.4), p=0.500) was similar after ingestion of GA and MM. There was a trend to less proximal reflux events with the alginate compared to the antacid (10.5 (8.9) vs 13.9 (8.3), p=0.070). No difference in the number of symptoms (5.0 (6.0) vs 4.2 (8.3), p=0.701) and reflux related symptoms (2.5 (4.0) vs 2.8 (5.6), p=0.988) was reported. Conclusion: Standard pH-impedance monitoring is suitable for clinical studies of reflux suppression in GORD patients. Distal reflux was similar but a trend to suppression of proximal reflux by GA compared to MM is present. This feasibility data indicates that trials will require 70 GORD patients to demonstrate effects (power 90%, p<0.05) on proximal reflux suppression after meals by alginates. More prolonged studies are required to assess effects on symptom control. Competing interests: R Sweis: None declared, A Anggiansah: None declared, T Wong: None declared, M Fox Grant/Research Support from: Reckitt Benckiser.